2021
DOI: 10.1136/bmjopen-2020-047199
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of correlates and prevalence of functional and high-risk multimorbidity in an academic HIV practice in New York City

Abstract: ObjectivesPeople with HIV have high levels of multimorbidity, but studies often focus on high-risk comorbidities such as hypertension or coronary artery disease. We examined both high-risk and functional comorbidities in an ethnically diverse clinic population to compare the prevalence of comorbidities and different patterns of multimorbidity.DesignRetrospective cross-sectional study.SettingUniversity-based primary care HIV clinic with two locations in New York City.ParticipantsPatients who had been seen by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…37 It has also been suggested that bidirectional influences between chronic conditions and age-related functional impairments can promote cellular senescence and mitochondrial dysfunction, increasing cardiovascular aging and impacting the health-related quality of life. 38 , 39 Ultimately, there is a need to better understand the ways in which chronic conditions, functional limitations, and mental health coexist to influence the risk of HF.…”
Section: Discussionmentioning
confidence: 99%
“…37 It has also been suggested that bidirectional influences between chronic conditions and age-related functional impairments can promote cellular senescence and mitochondrial dysfunction, increasing cardiovascular aging and impacting the health-related quality of life. 38 , 39 Ultimately, there is a need to better understand the ways in which chronic conditions, functional limitations, and mental health coexist to influence the risk of HF.…”
Section: Discussionmentioning
confidence: 99%
“…24 Yet another study classified comorbidities into high-risk comorbidity and functional comorbidity. 22 For older PLHIV, the latter defining classification of multimorbidity may correlate with the goals of care, as functional status impacts an individual's quality of life.…”
Section: Classification Of Multimorbiditymentioning
confidence: 99%
“…Some studies clustered comorbidities into categories of general medical conditions, and conditions seen in people who have HIV such as sexually transmitted diseases, substance use or their complications 24 . Yet another study classified comorbidities into high‐risk comorbidity and functional comorbidity 22 . For older PLHIV, the latter defining classification of multimorbidity may correlate with the goals of care, as functional status impacts an individual's quality of life.…”
Section: Classification Of Multimorbiditymentioning
confidence: 99%
See 1 more Smart Citation